Simulated Patients enhance Discharge Process - Maclean, Sharon; Geddes, Fiona; Kelly, Michelle; Della, Phillip (2016)
As hospital lengths of stay are reduced and patients are organised to return home with the expectation of managing more complex issues, preparing patients and their families for discharge becomes more challenging. Patients with chronic health conditions, such as type 2 diabetes typically have poorer health outcomes post discharge and higher readmission rates (Peter et al. 2015). Preparing nurses to perform safe, complex patient discharge will likely lead to improved patient confidence in self-management, and potentially better outcomes.